2007
DOI: 10.4103/0970-1591.32056
|View full text |Cite
|
Sign up to set email alerts
|

Premature ejaculation

Abstract: Premature ejaculation (PE) is a common male sexual disorder. Recent normative data suggests that men with an intravaginal ejaculatory latency time (IELT) of less than 1 minute have “definite” PE, while men with IELTs between 1 and 1.5 minutes have “probable” PE. Although there is insufficient empirical evidence to identify the etiology of PE, there is limited correlational evidence to suggest that men with PE have high levels of sexual anxiety and inherited altered sensitivity of central 5-HT (5-hydroxytryptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 83 publications
(120 reference statements)
1
16
1
1
Order By: Relevance
“…However, many questions about how drugs, especially herbal drugs, affect premature ejaculation remain unanswered. Meanwhile, studies indicated that the relief of mental problems and the prevention of serotonin reuptake such as the SSRIs with sedative properties can help to treat this disorder 39,[47][48][49][50] . Overall, medicinal plants are effective on sexual dysfunction via several mechanisms of action (Fig.…”
Section: Medicinal Plants Effective On Premature Ejaculationmentioning
confidence: 99%
“…However, many questions about how drugs, especially herbal drugs, affect premature ejaculation remain unanswered. Meanwhile, studies indicated that the relief of mental problems and the prevention of serotonin reuptake such as the SSRIs with sedative properties can help to treat this disorder 39,[47][48][49][50] . Overall, medicinal plants are effective on sexual dysfunction via several mechanisms of action (Fig.…”
Section: Medicinal Plants Effective On Premature Ejaculationmentioning
confidence: 99%
“…PE is associated with some psychosocial factors such as immature sexual technique, and low frequency of sexual activity (36). In dapoxetine clinical trials, a substantial proportion of patients in placebo group reported an improvement in IELT, which indicates that increased sexual frequency may have effect on ameliorating PE symptoms (12).…”
Section: Scheduled Follow-up Visitsmentioning
confidence: 99%
“…The prevalence of ED is significantly higher among men with hypertension than in general population [5][6][7][8][9]. A decrease risk of premature ejaculation (PE) has been reported in men with treated diabetes, while no association was found with hypertension, cardiac disease, hypercholesterolemia and peripheral or central neuropathy [10]. Few studies have been done on this topic in India and hence doing such a study in our setup will be helpful in identifying sexual dysfunctions in hypertensive male patients and treating this aspect of the disease as well.…”
Section: Introductionmentioning
confidence: 99%